Redesain Ruang Filing Rawat Jalan Berdasarkan Aspek Ergonomi di UOBK RSUD Dr. Mohamad Saleh Kota Probolinggo - Hariez, Tsalits Maulidah; Choirunisa, Vionanda; Sangkot, Hartaty Sarma (Politeknik Negeri Jember, 2024)
The storage space for outpatient medical record at UOBK RSUD Dokter Mohamad Saleh is not accordance with the ergonomic aspect because the distance between the shelves is too narrow, which is around 50-60 cm. This makes officers unable to collect medical record simultaneously with other officers, so that it can cause delays in the distribution of medical record files to multiple destinations. This study aims to redesign the spatial layout for storing outpatient medical record based on ergonomic aspects at the UOBK RSUD Dokter Mohamad Saleh. The type of research used is descriptive qualitative. The research instrument uses a checklist sheet and interview guide. The results of this study are a storage layout design with a storage space area of 36 m2 with the addition of room and shelves for inactive medical record, the distance between shelves is 900-100 cm which is in accordance with the standards and the addition of work equipment, namely shelves for inactive files, work table and one computer unit. The conclusion of this study is the redesign of the outpatient medical record storage layout trying to be able to meet the requirements according to standards and adjust conditions in the field, namely the addition of room area and shelves for inactive medical record and also the addition of work equipment.